Perancangan Buku Fotografi Destinasi Wisata Kuliner Legendaris di Kota Malang - Evelyne Cerelia Hadikusuma; Sultan Arif Rahmadianto; Didit Prasetyo Nugroho (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2022)
City of Culinary is the nickname of Malang City because within Malang City, there are lots of types of Culinary spots, including the legendary culinary destinations that has been around for decades. However, the popularity of modern café that keeps developing in the past few years can cause the fall of Malang City’s legendary culinary tour destination. Therefore, photography is used as the media that will gives information about the whereabouts of the legendary culinary destinations, so that people keep on knowing the legendary culinary destinations that exist, and those destinations still survive in this modern era. The design method that is used is a research method with qualitative approach. Through data collection such as interviews, observation, and documentation, a lot of datas was obtained to be analyzed to find the design concept of this photobook. The photobook concept obtained is photography, nostalgia, and cultural preservation. The genre that is used for this photography is food photography, where the photo results will be packed as a photobook with 10 legendary culinary destinations that has the dimension of 20 x 20 cm with 117 pages thick, printed in full color, and bounded with hardcover. Beside legendary food photo from those 10 legendary culinary destinations, this photobook is also consists of the short history from each of the legendary culinary, the legendary menu, and informations about the location of the places, accompanied with QR Code that is connected to Google Maps.